Beyond Lassa Fever: Systemic and structural barriers to disease detection and response in Sierra Leone - Rohan, Hana (PLOS Neglected Tropical Diseases, 2022)
Author summary Lassa fever (LF) often presents clinically as undifferentiated febrile illness. Lassa Fever cases in Sierra Leone have been falling since the 2014–2016 Ebola epidemic. Data from other LF-endemic countries suggest the drop in case numbers reflects reduced health seeking behaviour or issues within the surveillance, response and health systems. In Sierra Leone, many other diseases present with a similar early clinical picture, including COVID-19, meaning that findings from a case study of LF have wider applicability. There are no recent empirical studies of the functionality of Sierra Leone’s disease surveillance and response system. Qualitative analysis of policy documents and primary data collected from within the health system identified multiple challenges including: issues with the LF case definition, approaches to differential diagnosis, specimen transport and the provision of results, and ownership of laboratory data. These issues lead to delays in diagnosis, and potentially worse outcomes for individual patients, as well as affecting the system’s ability to respond to outbreak-prone disease.